Nusinersen treatment of spinal muscular atrophy: current knowledge and existing gaps - Gidaro, T; Servais, L (Wiley, 2018)
Spinal muscular atrophy (SMA) is a recessive disorder caused by a mutation in the survival motor neuron 1 gene (SMN1); it affects 1 in 11 000 newborn infants. The most severe and most common form, type 1 SMA, is associated with early mortality in most cases and severe disability in survivors. Nusinersen, an antisense oligonucleotide, promotes production of full-length protein from the pseudogene SMN2. Nusinersen treatment prolongs survival of patients with type 1 SMA and allows motor milestone acquisition. Patients with type 2 SMA also show progress on different motor scales after nusinersen treatment. Nusinersen was recently approved by the European Medicines Agency and the US Food and Drug Administration; it is now reimbursed in several European countries and in the USA. In Australia, the transition from expanded access programme to commercial availability is coming soon. In New Zealand, an expanded access programme is opened, and in Canada price negotiation for the treatment is in progress. In this review we exemplify the clinical benefit of nusinersen in subgroups of patients with SMA. Nusinersen represents the first efficacious marked approved drug in type 1 and type 2 SMA. Different knowledge gaps, such as results in older patients, in patients with permanent ventilation, in patients with neonatal forms, or in patients after spinal fusion, still need to be addressed. WHAT THIS PAPER ADDS: Identifies gaps in knowledge about the efficacy of nusinersen in broader populations of patients with spinal muscular atrophy. Identifies open questions in populations of patients where proof of efficacy is available.